Cancer in Africa: Is It a Genetic or Environmental Health Problem? - Bahnassy, Abeer A.; Abdellateif, Mona S.; Zekri, Abdel-Rahman N. (Frontiers in Oncology, 2020)
Patients of African ancestry have the poorest outcome and the shortest survival rates from cancer globally. This could be attributed to many variables including racial, biological, socioeconomic and sociocultural factors (either single, multiple or combined), which may be responsible for this major health problem. We sought to assess the most common types of cancer that endanger the health of the African people, and tried to investigate the real differences between African and other Non-African patients regarding incidence, prevalence and mortality rates of different cancers. Therefore, identifying the underlying aetiological causes responsible for the increased incidence and mortality rates of African patients will allow for changing the current plans, to make optimized modalities for proper screening, diagnosis and treatment for those African patients, in order to improve their survival and outcomes.